# Simple math problem, exponents

## Homework Statement

I am working on a physics problem, and am unsure of my math at one point. The physics problem is irrelevant, as I just want to verify my math. I am in calc3 and diff eq., I am just a little fuzzy/unsure of my algebra sometimes. Could someone please tell me if the work I have below follows the proper math/algebra rules? Thanks!

n/a

## The Attempt at a Solution

Let's say I have v^-1/3 = 2P/(AN) and I want to find out what v^2/3 is equal to. In order to do this, can I just raise both sides of the equation to the -2 power so that I get this: v^-2/3 = (2P/(AN))^-2 which simplifies to this: v^-2/3 = (AN/(2P))^2 right?

Related Precalculus Mathematics Homework Help News on Phys.org
Simon Bridge
Homework Helper
Let's say I have v^-1/3 = 2P/(AN) and I want to find out what v^2/3 is equal to. In order to do this, can I just raise both sides of the equation to the -2 power so that I get this: v^-2/3 = (2P/(AN))^-2 which simplifies to this: v^-2/3 = (AN/(2P))^2 right?
Let me rewrite all that more clearly and you can tell me if I have understood you:

You have $$v^{^-\frac{1}{3}}=\frac{2P}{AN}$$ and you want to find $$v^{^+\frac{2}{3}}$$ ...?

note: the rule you want is - $(v^a)^b = v^{ab}$ so $$(v^{^-\frac{1}{3}})^2 = v^{(^-\frac{1}{3}\times \frac{2}{1})} = v^{^-\frac{2}{3}}$$... or:$$(v^{^-\frac{1}{3}})^{^-2} = v^{(^-\frac{1}{3}\times ^- \frac{2}{1})} = v^{^+\frac{2}{3}}$$

Last edited:
Let me rewrite all that more clearly and you can tell me if I have understood you:

You have $$v^{^-\frac{1}{3}}=\frac{2P}{AN}$$ and you want to find $$v^{^+\frac{2}{3}}$$ ...?

note: the rule you want is - $(v^a)^b = v^{ab}$ so $$(v^{^-\frac{1}{3}})^2 = v^{(^-\frac{1}{3}\times \frac{2}{1})} = v^{^-\frac{2}{3}}$$... or:$$(v^{^-\frac{1}{3}})^{^-2} = v^{(^-\frac{1}{3}\times ^- \frac{2}{1})} = v^{^+\frac{2}{3}}$$
Sorry for the format, I'm still trying to figure out how to use latex. Yes, that is right. I am starting out with $$v^{^-\frac{1}{3}}=\frac{2P}{AN}$$ and I wanted to use $(v^a)^b = v^{ab}$ to find out what $$v^{^\frac{2}{3}}$$ is equal to in terms of P,A and N.

Therefore, $$v^{^\frac{2}{3}}=(\frac{AN}{2P})^{^2}$$ correct?

Mark44
Mentor
Sorry for the format, I'm still trying to figure out how to use latex. Yes, that is right. I am starting out with $$v^{^-\frac{1}{3}}=\frac{2P}{AN}$$ and I wanted to use $(v^a)^b = v^{ab}$ to find out what $$v^{^\frac{2}{3}}$$ is equal to in terms of P,A and N.
Therefore, $$v^{^\frac{2}{3}}=(\frac{AN}{2P})^{^2}$$ correct?
Yes.
v-1/3 = (2P)/(AN)
=> v1/3 = (AN)/(2P)

Now you can square both sides, getting the equation you show, above.

Yes.
v-1/3 = (2P)/(AN)
=> v1/3 = (AN)/(2P)

Now you can square both sides, getting the equation you show, above.
Great! Thank you!

Simon Bridge